The writing of the return in some postcolonial and english novels (Chimamanda Ngozi Adichie, Dany Laferrière, Alain Mabanckou, Léonora Miano, Taiye Selasi) - (:unkn) unknown (My University, 2022)
Obviously, if the world today is passed by a whole series of human exchange and flows, particularly due to various migrations, some political or ideological currents rather advocate a retreat into the national past and a return to tradition. In this context of conflicting tensions, this thesis examines the conditions of writing a novel of return by African writers or writers of African descent of the contemporary period. The corpus is made up of five postcolonial novels written by authors who have experienced the departure, the return and sometimes the round trip. They are Dany Laferrière (L’énigme du retour), Alain Mabanckou (Lumières de Pointe-Noire), Léonora Miano (Tels des astres éteints), Chimamanda Ngozi Adichie (Americanah) and Taiye Selasi (Ghana Must Go). The study focuses on the nature of colonial or postcolonial encounters in the Africa-Europe-America triangle and the conditions of exchange and sharing between the three worlds. The thesis also examines the mobility of postcolonial subjects and attempts to develop a typology of departures and returns represented as exile, migration or expatriation. Finally, the thesis considers the novel of return as conveying a poetics likely to shift postcolonial paradigm. The use of myths and legends, the questioning about identity through playing on filiation and affiliation, the implementation of intermedial practices participate in renewing the postcolonial scenography of the novels of return under study.
Keywords: African Research